India - Achieving the Millennium Development Goals (MDG) in India's Poor States : Reducing Child Mortality in Orissa - World Bank (Washington, DC, 2012)
This report builds on the World Bank's earlier report on the Millennium Development Goals (MDGs) in India (2004 report number 30266), which highlighted the challenges India faces in meeting a number of the MDGs. The report focuses on the state of Orissa and is organized as follows: the second chapter provides a brief background on Orissa. This is followed by a review of recent trends with infant and child mortality in the state. Chapter 4 introduces a framework for assessing the multitude of factors which have a bearing on infant and child mortality, dividing them into four groups: the individual woman/mother; the family; the community and service provision. Chapter 5 applies the analytical framework to Orissa and this is followed by a chapter 6 which looks at district level patterns. The final chapter of the report pulls it altogether and attempts to answer three questions: what is needed to bring down child mortality rates in Orissa and achieve the 11" Five Year Plan and MDG goal; how well are existing interventions placed to do the job; and where are the gaps and how can they best be filled. The report ends with an outline of a possible multi-sectoral program designed to reduce child mortality in Orissa.